Respuesta :
Answer: y = 2
Step-by-step explanation:
we need to use systems of equations, basically since we know what x equals, we plug that into first equation so:
since x=2y+1,
we can say that:
(2y+1)+2y=9
then we solve this equation,
first we expand the brackets- 2y+1+2y=9,
then we combine like terms- 4y+1=9
then we take 1 away from both sides- 4y=8
then we divided both sides by 4
y=2
Hope this helps xx
Answer:
- (5, 2)
Step-by-step explanation:
Given system:
- x + 2y = 9
- x = 2y + 1
Solve for y by substitution:
- (2y + 1) + 2y = 9
- 4y + 1 = 9
- 4y = 8
- y = 2
Find the value of x:
- x = 2*2 + 1
- x = 5